Recent advances in the biosynthetic pathway and structural modification of gentamicin - Chen, Xiaotang; Zou, Ruifen; Qian, Bao-Chen; Ni, Xianpu; Xia, Huanzhang (Frontiers in Microbiology, 2025)
As a member of the first-generation aminoglycoside antibiotics, gentamicin was once widely used in clinical practice. However, due to its drug resistance, toxicity, and side effects and the development of novel antibiotics, gentamicin has gradually faded from the spotlight. However, in recent years, aminoglycoside antibiotics have regained significant attention from the medical community as a critical therapeutic option for severe infections caused by multidrug-resistant bacteria. This review provides a detailed overview of the complete biosynthetic pathway of gentamicin and its recent advances, including the biosynthesis of the core structure 2-deoxystreptamine (2-DOS), the biosynthesis of the first pseudotrisaccharide intermediate gentamicin A2, the key branch point intermediate X2, and its parallel pathways. The methylation network, the transamination–epimerization network, and the di-deoxygenation processes within the gentamicin biosynthetic system are highlighted. Recent progress in the engineering of the gentamicin biosynthetic pathway and the development of novel gentamicin derivatives as new aminoglycoside antibiotics are also summarized. Finally, this review offers perspectives on the future research directions and uses of gentamicin. In summary, a detailed dissection of the complex biosynthetic network of gentamicin is provided to lay the groundwork for targeted and random structural modifications of gentamicin using combinatorial biosynthetic and high-throughput screening technologies to develop new aminoglycoside antibiotics with lower host toxicity and greater activity against resistant strains.